PERTANGGUNGJAWABAN PIDANA WISATAWAN YANG MERUSAK KELESTARIAN LINGKUNGAN WISATA - Saputra, Beri (Fakultas Hukum Universitas Bangka Belitung, 2017)
The aim of this study is to observe the enforcement of law and the criminal responsibility of tourists for tourism. Type of juridical normative study using juridical normative and juridical empirical methods. That the law is enforced when there is a violation of it, since the person committing the violation should be held accountable. The individual who can be held responsible is one who is mentally sane. The weight of the penalty is based on the elements of the violation